Development of interior design specifications for childhood development centers in Boac, Marinduque - Buenaventura, Bonn Alvin Magparangalan; Aquino, Pamela B. (Quezon City College of Home Economics, University of the Philippines Diliman, 2022)
The Department of Social Welfare and Development follows the “Standards for Day Care, Other ECCD Centers and Service Providers (For Children Aged 0-5.11 Years)” for the accreditation of Barangay Child Development Centers. From an Interior Design perspective, the standards detailed for Physical Environment and Safety, specifically the Indoor Environment, are insufficient in the current practices applied by selected Child Development Centers in Boac, Marinduque. Choi et al. (2014) presents the impact of Indoor Environment Quality on the learning perception of children where the design criteria is focused on Indoor Air Quality, Thermal Comfort, Aesthetic, Color, Acoustics, Light, Furnishings, and Fixtures. A descriptive research design using a multi-method approach which includes site documentation, literature research, and interviews were used for data gathering. Through purposive sampling, three (3) barangay centers representing the municipal legislative districts: Riverside, Seaside, and Ilaya, were selected using a criterion based on location, population, and floor area. These were assessed and evaluated to determine factors that would affect the development of design strategies that are socially and culturally appropriate by establishing the needs and resources of the responding Barangay Child Development Centers. The results showed problems related to funding due to government restrictions, resulting in a lack of resources to implement an appropriate and optimum learning environment. Moreso, inconsistencies in the interpretation of the provided standards were observed leading to the recommendation of design standards and guidelines for the Boac Child Development Centers in line with a progressive educational facility design practice for the town.
Thesis
Includes bibliographical references (pages 62-68)
Keywords: Interior decoration -- Philippines -- Boac (Marinduque); Decoration and ornament, Architectural, in interior decoration; Child development centers